Exploring electricity and magnetism - Solway, Andrew (New York : Rosen Central, 2008)
An exploration of electricity and magnetism that explains what they are and discusses circuits and batteries, household power supply, energy, and much more. Includes a glossary and resources.
Includes bibliographical references (p. 47) and index.
8.5
5-8
Keywords: Electricity -- Juvenile literature; Magnetism -- Juvenile literature; Electricity; Magnetism; Electricity; Magnetism